2011
DOI: 10.1097/mcg.0b013e318207f3cf
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Sessile Serrated Adenomas

Abstract: Our data suggest that smoking at least 20 pack-years is strongly associated with any and large SSAs. In addition, diabetes mellitus and obesity seem to be associated with SSAs as well. Our data has implications for CRC screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 0 publications
3
95
3
Order By: Relevance
“…There may be an increase of hypermethylation abnormalities in women smokers [13,[27][28][29], which may increase the risk for proximal neoplasia as well as serrated polyps. A recent case control study examining SSAs, most of which were proximal, observed an increased risk associated with smoking [30]. To examine this issue, we examined the risk for large proximal serrated lesions in our sample and observed that the risk for these lesions was increased in female smokers only.…”
Section: Discussionmentioning
confidence: 88%
“…There may be an increase of hypermethylation abnormalities in women smokers [13,[27][28][29], which may increase the risk for proximal neoplasia as well as serrated polyps. A recent case control study examining SSAs, most of which were proximal, observed an increased risk associated with smoking [30]. To examine this issue, we examined the risk for large proximal serrated lesions in our sample and observed that the risk for these lesions was increased in female smokers only.…”
Section: Discussionmentioning
confidence: 88%
“…18 On the contrary, Huang et al found no association between smoking and advanced serrated polyps. 19 Current smoking was associated with a significantly higher polyp number in patients with serrated polyposis, 16 and the prevalence of current smokers was higher among serrated polyposis patients than in the general population.…”
Section: Discussionmentioning
confidence: 97%
“…The association between smoking and SP risk was assessed by 29 articles which reported information from 29 studies, of which 26 articles investigated HP/SP risk 24,25, and six investigated SSA/P risk [29][30][31][51][52][53] . Most studies originated from the USA, five from Europe, and five in Asian populations (Supplementary Table 1(a)).…”
Section: Smokingmentioning
confidence: 99%